Teaching children with hearing impairments to labour - Bannayeva Matluba Olimdjan kizi (Genius Journals, 2021)
If we look at the history of deaf pedagogy, pedagogues and scientists J. Cordano, V.I.Flery, J.Itar, S.Speshnov, who studied children with hearing impairments as objects of research at different times, have a partial vocabulary that can understand the speech addressed. They noted that there are children who can compose even simple sentences, and that if the speech is addressed to them in an elevated manner, the problems of educating such children can be solved. R.M.Boskis believes that the key to the effectiveness of education for children with hearing impairments is the understanding of the developmental characteristics of this category of children
Keywords: Vocabulary; pedagogues and scientists J. Cordano; V.I.Flery; J.Itar